New Insights about the Selectivity in the Activation of Hydrogen Peroxide by Cobalt or Copper Hydrogel Heterogeneous Catalysts in the Generation of Reactive Oxygen Species - Lazaro Martinez, Juan Manuel (2016)
We report the performance of Co(II) and Cu(II) coordination complexes on H2O2 activation. The heterogeneous catalysts containing aliphatic amine, N-heterocycle, and/or carboxylic acid ligands in hydrogel materials coordinated with Co(II) or Cu(II) were used in this study. These complexes were characterized by solid-state NMR, X-ray photoelectron spectroscopy (XPS), and X-ray fluorescence techniques in order to quantify the superficial and bulk metal ion centers together with the aim of elucidating the ligands involved in the uptake of Co and Cu ions. The release of free radicals on H2O2 activation and the identity of reactive oxygen species were studied by spin trapping using DMPO in electron spin resonance (ESR) experiments. The Co(II) complex/H2O2 systems produced O2, anion superoxide (O2•–), and hydroxyl radical (OH•), which diffused into the solution at the time that a decrease in pH was detected. A possible catalytic mechanism would involve the Co(II)/Co(III) redox couple, according to XPS results. In the same way, the Cu(II) complex/H2O2 systems produced O2 and OH•, with evidence of Cu(II)/Cu(I) redox cycle. For these catalytic systems, there was no direct evidence of intermediary reactive species. The identity of the ligands played a crucial role in the efficiency of catalytic activation. In addition, in the absence of H2O2, the dissolved O2 was activated by most of the complexes tested, releasing only OH•.